Alterations of Gut Microbiome in Patients with Colorectal Advanced Adenoma by Metagenomic Analyses - , Jingyuan Xiang, Jingyuan Xiang, Ningli Chai, Longsong Li, Xinwei Hao, Xinwei Hao, Enqiang Linghu (Turkish Journal of Gastroenterology 1, 2024)
Background/Aims: Colorectal cancer (CRC) is one of the deadliest cancers worldwide, mostly arising from adenomatous polyps. Mounting evidence has demonstrated that changes in the gut microbiome play key roles in CRC progression, while quite few studies focused on the altered microbiota architecture of advanced adenoma (AA), a crucial precancerous stage of CRC. Thus, we aimed to investigate the microbial profiles of AA patients. Materials and Methods: Fecal samples were collected from 26 AA patients and 26 age- and sex-matched normal controls (NC), and analyzed by shotgun metagenomic sequencing. Results: Gut microbial dysbiosis was observed in AA patients with lower alpha diversity. Advanced adenoma was characterized by an increased Bacillota/Bacteroidota ratio and higher Pseudomonadota levels compared to normal individuals. Linear discriminant analysis effect size (LEfSe) analysis was performed and identified 14 microbiota with significantly different abundance levels between AA and NC groups. Functional analysis revealed that tryptophan metabolism was upregulated in AA. Correspondingly, the expressions of gut microbes implicated in tryptophan metabolism also changed, including Akkermansia muciniphila, Bacteroides ovatus, Clostridium sporogenes, and Limosilactobacillus reuteri. The microbial network suggested that AA exhibited decreased correlation complexity, with Escherichia coli and Enterobacteriaceae unclassified harboring the strongest connectivity. A diagnostic model consisting of 3 microbial species was established based on random forest, yielding an area under the curve (AUC) of 0.799. Conclusion: Our study profiled the alterations of the gut microbiome in AA patients, which may enrich the knowledge of microbial signatures along with colorectal tumorigenesis and provide promising biomarkers for AA diagnosis. Cite this article as: Xiang J, Chai N, Li L, Hao X, Linghu E. Alterations of the gut microbiome in patients with colorectal advanced adenoma by metagenomic analyses. Turk J Gastroenterol. 2024;35(11):859-868.